MONITORING KUALITAS LINGKUNGAN DALAM UPAYA IMPLEMENTASI PENGELOLAAN DAN PEMATAUAN LINGKUNGAN DI PT XYZ - Reni Masrida (Journal of Industrial and Engineering System, 2023)
The global decline in environmental quality includes direct and indirect impacts from industries that meet individual needs or complementary facilities. Industrial development is one of the support systems that plays a role in meeting these needs. One of the industries located in the bonded area in the Cikarang area produces sheet plastic goods industry in the form of Polycarbonate roofing. Related to this, PT XYZ (the initiator) in the implementation of its daily operations makes efforts to manage and monitor the quality of the environment so that it can be controlled and managed if it exceeds the permitted capacity or quality standards as regulated in the applicable laws and regulations in accordance with the affected environmental components or humans, in this case workers who are directly related to the production process. The research was conducted at PT XYZ which is located in the Industrial Estate, Cicau Village, Central Cikarang District, Bekasi Regency, West Java. The object of research is industrial environmental quality monitoring. The research method includes sampling of environmental quality at several monitoring points that can represent the impacts resulting from industrial activities, laboratory analysis, then the results of the analysis are compared with applicable regulations to further serve as a basis for decision making for no further or correction of environmental quality that has the potential to decline and needs improvement. The noise level at PT XYZ for monitoring semester 2, year 2022 where the noise level at 1 (one) monitoring point exceeds the quality standard but is still within the noise level tolerance of ± 3 dBA, namely the Crusher Area, 85.9 dBA respectively. The measured work environment climate in semester 2, year 2022 has increased for the Fisnish Good area and Crusher Area and has not increased significantly so that control efforts are needed, currently the installation of environmentally friendly solar cell panels has been carried out and is awaiting permission to be operationalized.